Shortened hospital length of stay and lower costs associated with rivaroxaban in patients with pulmonary embolism managed as observation status. Issue 1 (January 2017) - Weeda, Erin R.; Peacock, W. Frank; Fermann, Gregory J.; Baugh, Christopher W.; Wells, Philip S.; Ashton, Veronica; Crivera, Concetta; Wildgoose, Peter; Schein, Jeff R.; Coleman, Craig I.
Summary: Background: Unlike rivaroxaban, treatment of patients with pulmonary embolism (PE) with warfarin requires parenteral bridging and coagulation monitoring that may prolong length‐of‐stay (LOS) and increase hospital costs. Aims: The aim of this study was to compare LOS, hospital costs and readmissions in PE patients managed through observation stays treated with rivaroxaban or parenterally bridged warfarin. Methods: Premier Hospital claims data from November 2012 to March 2015 were used to identify patients with a primary diagnosis code for PE managed through an observation stay and with ≥1 claim for a PE‐related diagnostic test on day 0‐2. Rivaroxaban users, allowing ≤2 days of prior parenteral therapy, were 1:1 propensity‐score matched to patients receiving parenterally bridged warfarin. LOS, the proportion of encounters lasting >2 midnights, total hospital costs of the index visit and risk of readmission for venous thromboembolism (VTE) or major bleeding during the same month or 2 months subsequent to the index event were compared between matched cohorts using multivariable regression. Results: A total of 312 rivaroxaban users were matched to 312 patients receiving parenterally bridged warfarin. Rivaroxaban was associated with an average of 0.27‐day shorter LOS, a 52% decreased odds of an encounter lasting >2 midnights and a 403 mean reduction in costs vs parenterally bridged warfarin ( P ≤.002 for all). The readmission rate for VTE during the same or subsequent 2 months following the index PE was similar between cohorts ( P =.75). No patient in either cohort was readmitted for major bleeding. Conclusion: Rivaroxaban was associated with shortened LOS and lowered cost vs parenterally bridged warfarin in PE observation stay patients, without increases in the short‐term rate of complications or readmission.